Pengenalan dan Pelatihan Pembuatan Soal Asesmen Kompetensi Minimum (AKM) pada Guru-Guru Matematika SMP - Iin Ariyanti; Fithria Ulfah; Soraya Djamilah; Ahmad Lazwardi; Rahmatya Nurmeidina (BADAN PENERBIT STIEPARI PRESS, 2023)
Changes in government policy that abolished the national exam into a national assessment have an impact on teacher competencies that must be developed in preparing matters related to the national assessment. The Minimum Competency Assessment (AKM) field focuses on literacy and numeracy activities. Literacy is not only related to text but can be in the form of symbols, numbers, charts or graphs. Based on the results of research on AKM, it was stated that 12 out of 44 teachers as respondents had not yet prepared for AKM. Therefore, training to improve teacher competence in making AKM questions that focus on student numeracy needs to be carried out. This service was held at SMPN 1 Martapura and was attended by 30 teachers who were members of the Mathematics MGMP for SMPN Banjar Regency. The material presented in this activity was about the meaning and purpose of AKM, AKM components, forms of AKM questions, numeracy competency levels and links to AKM questions from the Ministry of Education and Culture. The results of the evaluation with a score of 4.13 for PkM participants showed that the participants were very satisfied with the training carried out.